2016
DOI: 10.2169/internalmedicine.55.6951
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Angioedema with Recurrent Abdominal Pain in a Patient with a Novel Mutation

Abstract: We describe a patient with hereditary angioedema type I. The patient had experienced recurrent abdominal pain around the time of her menstrual period for 13 years. A laboratory examination showed reduced functional and antigenic levels of C4 and C1 inhibitor (C1-INH). To establish a diagnosis, we carried out a DNA analysis of the patient's C1-INH gene. We determined that the patient was heterozygous for a single base pair transposition of T to C at nucleotide 4429 in exon 4, which had not been reported in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…7 In majority (80-85%) there is a reduction of both antigen and functional levels of Published literature on HAE from developing countries is very limited. [13][14][15][16][17][18][19][27][28][29] To the best of our knowledge, no long-term follow-up studies are available from India, especially in children. Moreover, there are limited data on genetic profile of patients with HAE from developing countries including India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In majority (80-85%) there is a reduction of both antigen and functional levels of Published literature on HAE from developing countries is very limited. [13][14][15][16][17][18][19][27][28][29] To the best of our knowledge, no long-term follow-up studies are available from India, especially in children. Moreover, there are limited data on genetic profile of patients with HAE from developing countries including India.…”
Section: Discussionmentioning
confidence: 99%
“…9-12 HAE has been reported infrequently from developing countries. [13][14][15][16][17][18][19][20][21] There are no long-term follow-up studies and no data on genetics of HAE from India. In this study we report our experience with HAE over last 2 decades.…”
Section: Introductionmentioning
confidence: 99%
“…Observations from 25 cases reported since 2010 support these findings 35–55. One study reported apparent improvements in the time from symptom onset to diagnosis for patients with a more recent year of birth compared with older patients 56.…”
Section: Delays In Diagnosis Of Haementioning
confidence: 88%